Zero waste for environmental sustainability: Exploring the enablers of the precycling lifestyle. - Hamzah, Nurul Amani; Badrul Hisham, Muhammad Faiq; Mohd Noor, Nurul Hidayana (Journal of Islamic, Social, Economics and Development, 2025)
recycling is a zero-waste approach to consumption that prevents waste by avoiding product packaging in the first place. Precycling is less applied in society because many people still need to learn about the concept, and most recyclables are thrown away and burned. Thus, the study examined the influence of materialism, consumer independence, environmental orientation, and voluntary simplicity on precycling behavior. A total of 300 respondents were randomly selected. Quantitative data is obtained through a question survey. Quantitative research findings are analyzed using correlation analyses and multiple regression. The study findings show significant relationships between materialism, consumer independence, environmental orientation, voluntary simplicity, and precycling. The most significant predictor of precycling was environmental orientation. The findings of this study can help the government and agencies to diversify promotions, campaigns, and activities to encourage the public to practice precycling.